1990
DOI: 10.1016/0014-5793(90)81421-j
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a highly reactive sulphydryl group in human placental glutathione transferase by a site‐directed fluorescent reagent

Abstract: A fluorescent maleimide derivative, N-(4-anilino-l-naphthyl) maleimide (ANM), a specific probe for thiol groups, reacted with human placental glutathione transferase (GST, EC 2.5.1.18), causing a complete inactivation of the enzyme in a few minutes. The modified enzyme was denatured, alkylated and digested with (L-l-tosylamide-2-phenylethyl chloromethyl ketone)-trypsin. The tryptic digest was analysed by HPLC and a fluorescent peptide was obtained. The sequence of this peptide allowed us, by a comparison with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 14 publications
(11 reference statements)
2
19
0
Order By: Relevance
“…The catalytic diversity of mammalian cytosolic GSTs, which can exist as homo-or heterodimers, arises in part from the existence of at least eight distinct classes (named Alpha, Kappa, Mu, Omega, Pi, Sigma, Theta, and Zeta) (1,4). The glutathione-binding site (G-site) and the catalytic mechanism of these enzymes have been the targets of many investigations involving chemical modification (5)(6)(7)(8), site-directed mutagenesis (9 -14), and x-ray crystallographic analysis (15)(16)(17)(18)(19)(20)(21). On the contrary, the electrophilic substrate-binding site (H-site) of GSTs is more complex and is class-specific.…”
mentioning
confidence: 99%
“…The catalytic diversity of mammalian cytosolic GSTs, which can exist as homo-or heterodimers, arises in part from the existence of at least eight distinct classes (named Alpha, Kappa, Mu, Omega, Pi, Sigma, Theta, and Zeta) (1,4). The glutathione-binding site (G-site) and the catalytic mechanism of these enzymes have been the targets of many investigations involving chemical modification (5)(6)(7)(8), site-directed mutagenesis (9 -14), and x-ray crystallographic analysis (15)(16)(17)(18)(19)(20)(21). On the contrary, the electrophilic substrate-binding site (H-site) of GSTs is more complex and is class-specific.…”
mentioning
confidence: 99%
“…Furthermore, no cysteine could be identified as a structural part of the active site and its non-essential character has been shown by site-directed mutation of class-n and class-p isoenzymes (Hsien et al, 1991 ;Tamai et al, 1991 ;Widersten et al, 1991). There is, however, a reactive cysteine, Cys45, about 1 nm away from the glutathione binding site (S,) whose integrity seems to be crucial for maintaining an active conformation (Lo Bello et al, 1990;Desideri et al, 1991 ;.…”
mentioning
confidence: 99%
“…Cysteine residues have been implicated in the catalytic activity of mammalian Piclass GST by a number of groups [16][17][18][19][20][21][22][23]. Chemical-modification and site-directed-mutagenesis studies showed that Cys%( in hGSTP1-1, mGSTP1-1 and rGSTP1-1 (Cys%& in pGSTP1-1) is responsible for enzyme inactivation, either by conformational changes or by preventing substrate binding [16][17][18][19][20][21][22][23]. The Cys%(, which is situated at the end of the α2 helix [10], near the GSHbinding site, may also undergo reversible oxidative inactivation by biological disulphides and thiol-group-containing compounds, forming an intra-or inter-subunit disulphide bond with Cys"!"…”
Section: Amphibian Embryo Glutathione Transferase: Amino Acid Sequencmentioning
confidence: 99%